Ответы и объяснения

Лучший Ответ!
  • Участник Знаний
2014-02-02T19:49:34+04:00
1) 4X^2 = X + 3
4X^2 - X - 3 = 0
D = 1 - 4*4*(-3) = 1 + 48 = 49 ; V D = 7 
X1 = ( 1 + 7 ) \ 8 = 1
X2 = ( - 6) \ 8 = ( - 0.75) 
Ответ + 1 и ( - 0.75 ) 
....................................................................
2) знаменатели ( Х + 2 ) равны 
Х + 2 не равен 0 ---> X не равен ( - 2 )
X^2 - 10 = 3X
X^2 - 3X - 10 = 0
D = 9 - 4*1*(-10) = 49 ; V D = 7 
X1 = ( 3 + 7 ) : 2 = 5
X2 = ( - 4 ) : 2 = ( - 2 ) - не подходит 
Ответ: + 5